Effectiveness of Educational Poster on Knowledge of Emergency Management of Dental Trauma–Part 1. Cluster Randomised Controlled Trial for Primary and Secondary School Teachers - Young, Cecilia (Public Library of Science, 2013)
OBJECTIVE: To investigate the effectiveness of educational posters in improving the knowledge level of primary and secondary school teachers regarding emergency management of dental trauma. METHODS: A cluster randomised controlled trial was conducted. 32 schools with a total of 515 teachers were randomised into intervention (poster) and control groups at the school level. Teachers’ baseline levels of knowledge about dental trauma were obtained by using a questionnaire. Posters containing information on dental trauma management were displayed in the school medical room, the common room used by staff, and on a notice board for 2 weeks in each school of the intervention group; in the control group, no posters were displayed. Teachers in both groups completed the questionnaire after 2 weeks. RESULTS: The teachers in the intervention schools (where posters were displayed for 2 weeks) showed statistically significant improvement in scores in cases where they had not previously learned about dental emergencies from sources other than first aid training, with an average score increase of 2.6656 (score range of questionnaire, −13 to 9; p-value <0.0001). CONCLUSION: Educational posters on the management of dental trauma can significantly improve the level of knowledge of primary and secondary school teachers in Hong Kong. KClinicalTrials.com HKCTR-1307 ClinicalTrials.gov: NCT01707355